THE CONFLICT OF THE MAIN CHARACTER IN SHAKESPEARE NOVEL HAMLET - Margareta Lughu, Maryam (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The title of this research the conflict of the main character in Shakespeare novel Hamlet. It aims to identify and classify the conflict of the main character and analyze the way the main character solve the conflict in the novel Hamlet written by Shakespeare. In this research, the researcher analyze from the side of literary work and reveal the type of conflict in the novel. It is qualitative and it uses library research as the method of the research. The data are taken from the novel of Hamlet which has 477 pages from e-book and other books or another articles as supporting data. The researcher does some steps in doing this research, that is : collecting the data, read the novel and some books related to the research, identify and classify the data (conflict of the character), analyze the data and draw the conclusion. Based on the result of the research, there are 3 types of the conflict found at the main character Hamlet, there are : Men vs Self, Men vs Men and Men vs Social life out.